2017
DOI: 10.26444/jpccr/80986
|View full text |Cite
|
Sign up to set email alerts
|

Mental adaptation to cancer in women with gynaecological cancer

Abstract: Kupcewicz E, Olewińska J, Pikus H, Jóźwik M. Mental adaptation to cancer in women with gynaecological cancer. J Pre-Clin Clin Res. 2017; 11(2): 120-126. doi: 10.26444/jpccr/80986 Abstract Introduction and objective. Adapting to gynaecological cancer is the problem of accepting and coping with the disease and its consequences. The aim of this study is to analyze the relationship between stress intensity and strategies for coping with stress and psychological adaptation to disease in women diagnosed with gynaeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…In our study the group of subjects was also comprised largely of patients with uterine cancer (71.6%). The average age of the participants in Kupcewicz et al’s study [ 33 ] was 56.10 years (SD = 10.75), which is similar to the average age of the participants in our study (M = 60.31; SD = 11.72). Kupcewicz et al’s study [ 33 ] revealed that the scores for the constructive style domain (43.5 ± 5.76) were significantly higher than those for the destructive style (21.7 ± 5.28).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our study the group of subjects was also comprised largely of patients with uterine cancer (71.6%). The average age of the participants in Kupcewicz et al’s study [ 33 ] was 56.10 years (SD = 10.75), which is similar to the average age of the participants in our study (M = 60.31; SD = 11.72). Kupcewicz et al’s study [ 33 ] revealed that the scores for the constructive style domain (43.5 ± 5.76) were significantly higher than those for the destructive style (21.7 ± 5.28).…”
Section: Discussionsupporting
confidence: 88%
“…The average age of the participants in Kupcewicz et al’s study [ 33 ] was 56.10 years (SD = 10.75), which is similar to the average age of the participants in our study (M = 60.31; SD = 11.72). Kupcewicz et al’s study [ 33 ] revealed that the scores for the constructive style domain (43.5 ± 5.76) were significantly higher than those for the destructive style (21.7 ± 5.28). This means that the studied women chose active approaches to the disease, such as a fighting spirit (M = 21.6 ± 3.47) and positive re-evaluation (M = 21.9 ± 3.01) [ 33 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, the mean for the constructive style (M = 43.5, SD = 5.76) in these patients was much higher than for the destructive style (M = 21.7, SD = 5.28). The study conducted by indicated that older patients obtained lower values in the area of fighting spirit and higher in the areas of helplessness-hopelessness and anxiety than the younger patients [22,23]. Juczyński Z.…”
Section: Discussionmentioning
confidence: 99%